Sistem Notifikasi Kondisi Cuaca Untuk Keselamatan Take Off Paralayang Menggunakan Metode Naive Bayes (Studi Kasus: Paralayang Gunung Banyak, Batu) - Muhammad Fajaruddin Akbar; Dahnial Syauqy; Gembong Edhi Setyawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Paragliding is a free-flying sport using cloth wings (parachutes) that take off and land using legs that use the wind, the wind itself has several types including dynamic lift and thermal lift. The wind in the paragliding take-off area is very important for athletes and tourists who will take off. The lack of information obtained in the take-off paragliding area, especially for most people (tourists) who want to fly, has difficulty getting wind information in the paragliding take-off area. From this problem, this research was conducted to determine the wind conditions in the form of notifications using 3 parameters, namely wind speed, wind direction and the presence of raindrops and then processed using the naive bayes method on the microcontroller that produces safe, alert and hazardous output. The wind speed sensor uses a rotary encoder which has an accuracy rate of 96.4% compared to the existing anemometer, in wind direction reading using a dual axis module which has a degree difference of 7.75 Â° and on a rain sensor, the sensor can detect well the presence of raindrops with the results of the whole system compared to the actual situation has an accuracy rate of 85.71%.